Impact of Bee Species and Plant Density on Alfalfa Pollination and Potential for Gene Flow - Johanne Brunet; Christy M. Stewart (Psyche: A Journal of Entomology)
In outcrossing crops like alfalfa, various bee species can contribute to pollination and gene flow in seed production fields. With the increasing use of transgenic crops, it becomes important to determine the role of these distinct pollinators on alfalfa pollination and gene flow. The current study examines the relative contribution of honeybees, three bumble bee species, and three solitary bee species to pollination and gene flow in alfalfa. Two wild solitary bee species and one wild bumble bee species were best at tripping flowers, while the two managed pollinators commonly used in alfalfa seed production, honeybees and leaf cutting bees, had the lowest tripping rate. Honeybees had the greatest potential for gene flow and risk of transgene escape relative to the other pollinators. For honeybees, gene flow and risk of transgene escape were not affected by plant density although for the three bumble bee species gene flow and risk of transgene escape were the greatest in high-density fields.